The relationship between sex-role identity, locus of control and self-concept amongst adolescent females within a historically disadvantaged community - Mukheibir, Susan C.(Susan Candace) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1994.